The coffins of Little Hope - Schaffert, Timothy. (Unbridled Books, 2011)
Essie is the octogenarian obituary writer for her family's small town newspaper. When a young country girl is reported to be missing, perhaps whisked away by an itinerant aerial photographer, Essie stumbles onto the story of her life. Or, it all could be simply a hoax, or a delusion, the child and child-thief invented from the desperate imagination of a lonely, lovelorn woman. Either way, the story of the girl reaches far and wide, igniting controversy, attracting curiosity seekers and cult worshippers from all over the country to this dying rural town. And then it is revealed that the long awaited final book of an infamous series of Y.A. gothic novels is being secretly printed on the newspaper's presses. The Coffins of Little Hope tells a feisty, energetic story of characters caught in the intricately woven webs of myth, legend and deception even as Schaffert explores with his typical exquisite care and sharp eye the fragility of childhood, the strength of family, the powerful rumor mills of rural America, and the sometimes dramatic effects of pop culture on the way we shape our world.